Association between maternal perceived capacity in life and physical punishment of teenage children: a longitudinal analysis of a population-based cohort in Tokyo, Japan. Issue 3 (17th March 2022) - Nakanishi, Miharu; Yamasaki, Syudo; Niimura, Junko; Endo, Kaori; Nakajima, Naomi; Stanyon, Daniel; Baba, Kaori; Oikawa, Nao; Hosozawa, Mariko; Ando, Shuntaro; Hiraiwa-Hasegawa, Mariko; Kasai, Kiyoto; et al.
Abstract : Objectives: Perceived capacity denotes a subjective sense of having resources to cope with strains and hardships, and hence maternal perceived capacity may be protective against risk factors for child maltreatment. This study investigated the longitudinal association between maternal perceived capacity in life and child maltreatment. Design: This population-based longitudinal study used self-reported questionnaires from the Tokyo Teen Cohort study (TTC), a large community-based cohort study conducted in Japan between 2014 and 2019. Setting: Mother–child pairs were randomly recruited from the resident registries of three municipalities in Tokyo, Japan. Methods: A total of 2515 mothers participated. Mothers' perceived capacity in life was evaluated using the self-reported TTC wave 2 survey when their children were 12 years old. Mothers rated the extent to which they had capacity in terms of time, finance, physical well-being, mental well-being and life in general. Physical punishment, which is linked to more severe childhood maltreatment, was assessed using a question about the use of physical punishment at the wave 3 survey when children were 14 years old. Results: After controlling for baseline covariates (including maternal social support, age, marital status, annual household income, educational attainment, child's age, gender, sibling and birth order, and behavioural difficulties), higher perceived capacity in finance (OR 0.95, 95% CI 0.90 to 0.99, p=0.026) and mental well-being (OR 0.93, 95% CI 0.88 to 0.98, p=0.005) were associated with less frequent use of physical punishment with 14-year-old children. Conclusions: Maternal perceived capacity in finance and mental well-being may decrease the risk of frequent use of physical punishment at the 2-year follow-up. Child maltreatment prevention strategies should aim to empower mothers and promote their perceived capacity in financial management and mental health.